Role of Mitochondria in Alzheimer ́s Disease - Ortiz, Genaro Genaro Gabriel; Pacheco-Moisés, Fermín; García-Trejo, José de Jesús; González-Castañeda, Roció E.; Macías-Islas, Miguel A.; Cruz-Ramos, José A.; Velázquez-Brizuela, Irma E.; Merino, Elva D. Árias; Rosa, Alfredo Célis de la (IntechOpen, 2011)
None